COMMUNICATION RISKS AND WAYS TO OVERCOME THEM IN THE DIGITAL WORLD - DEKALIUK, Olena; FEDORYSHYNA, Larysa (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The relevance of the topic of the article is due to the fact that managing communication risks in the digital environment today is becoming a strategic task for any enterprise. The purpose of the article is to study communication risks in the activities of enterprises and outline ways to minimize and overcome them in the digital environment. The following general and special research methods were used to achieve the set goal, in particular: analysis, monographic, abstract-logical, generalization- to consider the essence of communication risks, determine their varieties, formulate ways to minimize risks when carrying out communications in the modern digital world; graphic and tabular- to clearly present the results of the research. It is substantiated that in modern conditions, communication risks are taking on new forms and scales, covering both individual and social levels of interaction. Among the main types of risks in the digital environment, the following can be distinguished: cybersecurity; fake information and disinformation; loss of trust in digital channels; excessive transparency and the risk of privacy violation; dependence on digital platforms; information overload (infonoise); digital inequality. Information imbalance, cultural incompatibility, communication inertia and manipulative communication are identified as types of communication risks in business relationships. The impact of CRM, ERP and analytical platforms on transparency and the level of trust in partner communications is analyzed. A system of basic criteria for assessing the effectiveness of communications is formed. It is substantiated that minimizing communication risks in the digital world requires a combination of technical solutions (cyber protection), organizational measures (regulations, policies), social tools (media literacy, ethics) and flexible reputation management.